Benefit of Combined Triiodothyronine (LT3) and Thyroxine (LT4) Treatment in Athyreotic Patients Unresponsive to LT4 Alone - Solter, D.; Solter, M. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Despite some reports, the usefulness of levothyroxine ( LT4) and levotriiodothyronine (LT3) combination therapy in hypothyroidism remains controversial. The objective of this paper is to study a benefit of additional LT3 in athyreotic patients who failed to normalize TSH on LT4 alone even with hyperthyroid serum T4 values.In a survey of 200 athyreotic patients treated between 2006 and 2009, about 7% failed to normalize serum TSH levels following treatment with LT4, though serum T4 values in the hyperthyroid range were achieved. These patients (characterized by serum T4≥160 nmol/L and TSH≥5.0 mIU/L), were additionally treated with 10 μg b. i. d LT3. LT3 and LT4 combination therapy resulted in decreased serum TSH levels into the normal range (12.8 vs. 1.22 mIU/L; p<0.01) and reduced LT4 dose (153.3 vs. 117.5 μg; p<0.01) required for normalization of serum T4 values (170.6 vs. 123.3 nmol/L; p<0.01). Serum T3 values were higher (1.3 vs. 2.26 nmol/L; p<0.01) than those during monotherapy with LT4.Our results indicate a subpopulation of athyreotic patients that could significantly benefit from combined LT4 + LT3 therapy in restoring normal TSH and thyroid hormone patterns. Further research should be undertaken to provide a genetic basis for these findings.
Keywords: thyrotropin; insufficiencies; thyroid